Determinants of job waiting period for economics graduates: An integration of human resource management and the Islamic perspective of silaturahmi (networking) - Siti Hardiyanti; Armelly Armelly (Privietlab, 2026)
This study analyzes the determinants of job waiting periods among bachelor graduates of the Faculty of Economics and Business at the University of Bengkulu, integrating human resource management and the Islamic concept of silaturahmi (networking). Primary data were collected from 40 respondents through structured questionnaires and in-depth interviews. A descriptive analysis using cross-tabulation and Likert scale measurements was applied to examine the influence of wages, age, and networking on graduates’ job search duration. The results indicate that networking, representing silaturahmi, is the most influential factor in shortening the waiting period, with 17.5% of graduates having six to eight professional contacts. Wage expectations also affect the duration, as some graduates prefer to wait for higher compensation (15% received IDR 1,000,000–1,490,000), while age has a comparatively smaller impact, with most graduates securing employment at 22 years old (25%). These findings highlight the importance of strengthening social ties and professional networks to enhance graduate employability and facilitate smoother transitions into the labor market. This study uniquely integrates human resource management principles with the Islamic concept of silaturahmi, offering new insights into strategies for enhancing graduate employability.